Impacts of contract farming on asset accumulation of malt barley farmers in Northwestern Ethiopia - Abebe Dagnew Koye; Degye Goshu; Lemma Zemedu Seifu; Million Sileshi (Cogent Economics & Finance, 2023)
Agriculture is the mainstay of the Ethiopian economy. Barley, including food and malt barley, is one of the major cereals produced by smallholder farmers. Though malt barley is the fastest-growing industry, demand is outpacing supply. As a result, Ethiopia is a net importer of raw malt barley. Recently, contract farming was implemented to address this issue in malt barley-potential areas. It has been one of the strategies utilized to enhance the commercialization of malt barley and replace imported malt barley, besides solving production and marketing challenges. The predicted results also include satisfying domestic malt barley demand, enhancing the welfare of smallholder farmers, and conserving the nation's foreign exchange. Although not thoroughly investigated, the research area has a low rate of CF participation and a low malt barley yield. Furthermore, previous research has focused on the CF impact of income, food security, and yield indicators of welfare, but no attention has been devoted to the implications of asset accumulation, which is a greater long-term indicator of welfare. Given the issues and research gaps identified, this study seeks to evaluate the impact of CF on malt barley farmers' asset accumulation in Northwestern Ethiopia. The data were collected from 398 samples in two districts, selected using multistage sampling techniques. The endogenous switching regression (ESR) model was used to account for bias coming from both observable and unobservable sources. For malt barley farmers, the average treatment effect on treated and untreated was 9652.7ETB and 7417.3ETB, respectively, and was significant at 1%. The base heterogeneities for CF participation and non-participation were 886ETB and −1349.4ETB, respectively. The average transitional heterogeneity was 2235.4ETB and statistically significant at 1%. Consequently, malt barley CF participation has a positive association with asset accumulation; this result supports transaction cost economic theory. Cooperative membership, off-farm employment, and age were all positively associated with the propensity to increase asset accumulation. The finding also reveals that land affected participants, whereas credit, household size, and farming experiences had a significant and positive effect on non-participants' assets. This shows that the asset accumulation of the two groups was determined by common variables with different magnitudes and different variables. Therefore, the concerned bodies should consider these heterogeneities to strengthen and improve the CF participation of malt barley farmers as long as they are adjusted to local conditions. Furthermore, spillover effects of CF on other sectors (other crops and the environment) and non-participants should be considered to check whether it has negative or positive external effects.
Keywords: 330; asset accumulation; contract farming; endogenous switching regression; malt barley